LEGAL ISSUES ON THE IMPLEMENTATION OF THE BLUE ECONOMY IN INDONESIA - Raden Yoseph Gembong Rahmadi (Journal Philosophy of Law, 2021)
The purpose of this study is to determine the legal regulation arrangements concerning the blue economy and solutions to overcome obstacles to the implementation of the blue economy, in this case, are B3 and dumping. This research is normative juridical research, using a descriptive method with a qualitative approach. The data source used in this study is secondary legal material, which will examine positive legal norms. The conclusion that can be stated is that there is no harmonization between articles in one law and harmonization between laws governing environmental management. The solution to overcome obstacles to implementing the blue economy is first to harmonize related legislation. Second, strict legal action and sanctions from the government if there are violations related to marine affairs. Third, the existence of joint patrols between related institutions in the country and patrols between countries.